Longing for normalcy in couple relationships: How chronic illness and care dependency change the relationship of long-married couples - Niedling, Katharina; Hämel, Kerstin (Frontiers in Public Health, 2023)
Coping with chronic illness and care dependency in a marital dyad challenges many older couples. In our qualitative research study, we are interested in how long-married spouses in Germany experi-ence their couple relationship while dealing with long-term care and adapting everyday life to home nursing. We conducted problem-centred interviews with 17 spouses according to the interpretive-reconstructive documentary method. We derived four thematic areas: 1. partner(ship) disappears behind the disease; 2. partners struggle with changing tasks and roles; 3. caring partners mourn the loss of intimacy; and 4. partners strive to rebalance the partnership. When chronic illness and care dependency enter couples’ lives, the self-image as husband or wife is affected. Nurses should be sensitive to the specific constellation of care in couple relationships and recognize the significance of this dyadic relationship as living in a satisfying couple relationship is essential for the health and well-being of both partners.